Socialism in the United States - Smith, Fredrick John (My University, 1895)
Introduction: It seems almost incredible that in a country where there is freedom with all its attendant advantages and possibilities; where there is such an immense acreage of tillable land; where not only the precious metals, gold and silver, but also the more common ones, lead, iron, copper, and zinc are dug from the earth in such abundance; where the school system approaches the ideal; where religion and politics are matters of opinion; in a word in a country where all those things are present which make for man’s happiness and well being, there should be a feeling of unrest among its people. This, nevertheless, is the case in our land today. There has for years past been brewing a conflict in which has been arrayed on the one hand the laborer and the employed on the other the capitalist and the employer. Reasons for this conflict have been given by various schools of thinkers, prominent among them being the class called socialists, who hold that all this difference is attributable to capitalistic productions in competition in other words. Ever since the socialist have made their appearance in the United States there have been vague and erroneous ideas as to what their teachings are. They have been accused of holding every kind of belief, from the most absurd to those so impracticable that they could only have originated in the mind of one demented. By many they have been classed side by side with the anarchist, when the fact of the matter is that these two schools are diametrically opposite. The one would abolish all government, while the other would place all power in the hands of government. This confusion is no doubt due as much to the lack of unity among those professing to be socialists as to a lack of understanding on the part of the people.
Citation: Smith, Fredrick John. Socialism in the United States. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Socialism; United States; Theses; Manuscripts (documents)